Additive rank-one preservers on block triangular matrix spaces - CHOOI, W; LIM, M (2006)
In this note, we address a description of the general form of additive rank-one preservers on block triangular matrix spaces over an arbitrary field. As an application, we characterize additive mappings preserving rank-additivity on block triangular matrix algebras. (c) 2005 Elsevier Inc. All rights reserved.